Hazard identification and risk characterization of bisphenols A, F and AF to aquatic organisms. (May 2016) - Tišler, Tatjana; Krel, Alja; Gerželj, Urška; Erjavec, Boštjan; Dolenc, Marija Sollner; Pintar, Albin
Abstract: Production of bisphenol A (BPA) analogues such as bisphenol F (BPF) and bisphenol AF (BPAF) has recently increased, due to clear evidence of adverse effects of BPA on humans and wildlife. Bisphenols (BPs) have already been released into aquatic environment without previous available information about potential adverse effects of BPs and their potential risk to aquatic ecosystems. In this study, lethal and sublethal effects of BPF and BPAF to bacteria, algae, crustacea and fish embryos were investigated and the results were compared to the adverse effects obtained for BPA. We found that BPAF was the most toxic compound to Daphnia magna, Danio rerio and Desmodesmus subspicatus ; the lowest 72 h EC50 (median effective concentration) and 21 d NOEC (no observed effect concentration) values were determined at 2.2 mg/L regarding zebrafish hatching success and 0.23 mg/L of BPAF obtained for growth and reproduction of water fleas, respectively. In most cases, BPA was more toxic to D. magna, D. rerio and D. subspicatus in comparison to BPF, but pigmentation of zebrafish embryos after 48 h of exposure and reproduction of water fleas after 21-day D. magna reproductive test exposure to BPF were much more impaired. Risk quotients (measured environmental concentration/21 d NOEC) showed that BPA, BPF and BPAF are recently not chronically hazardous to the survival, reproduction and growth of water fleas in surface waters. On the other hand, we importantly show that currently present BPAF concentrations in surface waters could cause a potential ecological risk to aquatic organisms. In the near future, higher concentrations of BPF and BPAF in surface waters are anticipated and for this reason further testing using test systems with various aquatic species and endpoints are needed to provide additional information about toxic impacts of BPF and BPAF on aquatic biota. Highlights: Higher toxicity of BPAF in comparison to BPF and BPA. BPA was more toxic to the majority of tested organisms in comparison to BPF. BPAF could cause ecological risk to aquatic organisms. Industrial replacement of BPA with BPAF is questionable. Abstract : We reveal that BPAF was found to be more toxic to tested organisms than BPA and BPF and it could cause ecological risk to aquatic organisms.